The Impacts of Harvesting Activities on Prey-Predator Fishery Model in the Presence of Toxin - Ang, Tau Keong; M. Safuan, Hamizah; Kavikumar, J. (Journal of Science and Technology, 2018)
The present paper discusses a prey-predator fishery model where both species are subjected to harvesting effort. Both species release some toxic substances to each other. The prey species obeys the law of logistic growth. The model is a modified version from the classic Lotka-Volterra predator-prey model. The equilibria of the model are obtained and the dynamical behaviors of the proposed system are examined. Simulations of the model are performed and bifurcation diagrams are studied. The effects of harvesting and toxin on the stability of steady states are examined. In the present research, we found that the impact of harvesting activities is more influential on the dynamical behaviors in the fishery model than that of the toxin.